Deconstructing Exceptionalism : Surveying Afro-Swedish Feminist Perspectives on Swedish State Feminism - Bullock, Lukas ; 0000-0002-0677-6833 (Social Politics: International Studies in Gender, State and Society, 2025)
The Swedish state has consistently used feminism as a grounding point in domestic and foreign policy frameworks. Gender equality considerations are central in structuring Sweden’s public sector, and figure as a key component of its exceptionalist self-image. However, minority groups have critiqued the ways that their lived experiences fail to be accounted for in policy processes. This points to tensions in the ways that marginalized groups are disenfranchised in the formation of state feminist policy as Sweden continues to frame itself as trailblazer when it comes to human rights and gender equality. This article considers how Afro-Swedish feminists interpret Swedish state feminism as a political project. Drawing from ethnographic fieldwork that engaged with Black feminists across Sweden, this article traces how these actors experience, interpret, and contest Swedish state feminist policy. As the article argues, the perspectives of Afro-Swedish feminists underscore the limitations of Sweden’s claim to feminist exceptionalism.